2007
DOI: 10.1007/s00266-006-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Satisfaction and the Patient’s Body Image, Life Satisfaction, and Self-Esteem: A Retrospective Study Comparing Adolescent Girls and Boys After Cosmetic Surgery

Abstract: Adolescents are good candidates for cosmetic surgery, but patients must be evaluated carefully. Any suspicion about a patient's psychological status must result in a psychiatric consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The question that research has yet to fully address is whether or not cosmetic surgery can actually improve the pervasive negative perceptions that young women have of their bodies (Cook et al 2006;Rodin 1993;Rodin et al 1985;Tiggemann 1994). Although some research suggests that cosmetic surgery may provide benefits to young women's body image (Kamburoglu and Ozgur 2007), it is also possible that the increasing rates of cosmetic surgery will exacerbate young women's body dissatisfaction by perpetuating an increasingly stringent ideal of attractiveness (Bordo 2003;Brumberg 2000). Some scholars have suggested that psychological screening should precede cosmetic surgery procedures (e.g., Zuckerman and Abraham 2008); our research could inform efforts to screen potential patients.…”
Section: Resultsmentioning
confidence: 97%
“…The question that research has yet to fully address is whether or not cosmetic surgery can actually improve the pervasive negative perceptions that young women have of their bodies (Cook et al 2006;Rodin 1993;Rodin et al 1985;Tiggemann 1994). Although some research suggests that cosmetic surgery may provide benefits to young women's body image (Kamburoglu and Ozgur 2007), it is also possible that the increasing rates of cosmetic surgery will exacerbate young women's body dissatisfaction by perpetuating an increasingly stringent ideal of attractiveness (Bordo 2003;Brumberg 2000). Some scholars have suggested that psychological screening should precede cosmetic surgery procedures (e.g., Zuckerman and Abraham 2008); our research could inform efforts to screen potential patients.…”
Section: Resultsmentioning
confidence: 97%
“…This finding is in accord with some and in contrast with a few other studies. For instance, some evidence show that cosmetic surgery helps in improving body image (Crerand, Franklin, & Sarwer, 2008;Soest, Kvalem, Roald, & Skolleborg, 2009;Kamburoglu & Figen, 2007) and health-related quality of life and self esteem (Neto et al, 2007). However, there are some other studies demonstrating that cosmetic surgery did not have a significant effect on self-esteem, quality of life or life satisfaction (Crerand, Franklin, & Sarwer, 2008;Soest, Kvalem, Roald, & Skolleborg, 2009;Meningaud et al, 2003;Bolton, Pruzinsky, Cash, & Persing, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(Ferraro, Rossano, & Andrea, 2005). Cosmetic surgery candidates all share a defective body image and are not satisfied with their self-perception (Ferraro, Rossano, & Andrea, 2005;Kamburoglu & Figen, 2007;. Body image is a significant part of self-conceptualization and has 2 domains namely ideal self-conceptualization and perceived selfconceptualization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the plastic surgeon it is always necessary to evaluate whether there is a real need to correct unpleasing features or if the request is a result of dysmorphophobia without objective problems. In the absence of appropriate global assessment, it cannot be determined whether such a surgical procedure would be beneficial [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%